Sudden Sensorineural Hearing Loss: Comparative Study of Different Treatment Modalities - Khater, Ahmed; El-Anwar, Mohammad Waheed; Nofal, Ahmad Abdel-Fattah; Elbahrawy, Atef Taha (International Archives of Otorhinolaryngology, 2018)
Introduction Idiopathic sudden sensorineural hearing loss (ISSNHL) is hearing loss of at least 30 dB in at least 3 contiguous frequencies within at least 72 hours. There are many different theories to explain it, and many different modalities are used for its management, such as: systemic steroids (SSs), intratympanic steroid injection (ITSI), hyperbaric oxygen therapy (HOT), antiviral drugs, and vasodilators or vasoactive substances.Objectives This study aims to evaluate the efficacy of the combination of the most common treatment modalities of ISSNHL and to compare the results if HOT was not one of the treatment modalities administered.Methods The study was conducted with 22 ISSNHL patients with ages ranging from 34 to 58 years. The patients were divided into 2 groups; group A included 11 patients managed by SSs, ITSI, antiviral therapy, and HOT simultaneously, and group B included 11 patients exposed to the aforementioned modalities, with the exception of HOT.Results After one month, all of the patients in group A showed total improvement in hearing in all frequencies, with pure tone average (PTA) of 18.1 ± 2.2, while in group B, 5/11 (45.5%) patients showed total improvement, and 6 /11 (54.5%) patients showed partial improvement, with a total mean PTA of 28.1 ± 8.7.Conclusion The early administration of HOT in combination with other clinically approved modalities (SSs, ITSI, antiviral therapy) provides better results than the administration of the same modalities, with the exception of HOT, in the treatment of ISSNHL.
Keywords: hearing loss; hyperbaric oxygen therapy; steroids; intratympanic injection